(untitled) (The Research of Medical Science Review, 2025)
Objective: To determine the association and impact of serum lactate on outcome and ICU-mortality in patients with Sepsis and Septic shock Study Design: Prospective Cohort study Place and Duration of Study: Department of Medicine and Intensive Care, Abbottabad, from 7 Feb 2025 to 7 June 2025. Methodology: Patients of either gender with age 18-65 years admitted with sepsis or septic shock in medical HDU and ICU were included in study. SOFA score, APACHE II score and serum lactate levels were noted within first 24 hours of admission. Impact of serum lactate on disease severity and association with in-hospital mortality was analyzed with Odds ratio. Results: Three hundred patients admitted with sepsis were included with mean age of 46.93 ± 13.35 years. Respiratory system was most common focus of infection in 110 (36.7%) patients, followed by gastrointestinal in 73 (24.3%). Higher lactate levels were significantly associated with increased mortality (p<0.0001). Patients with severely elevated lactate had 3.98 times higher odds of death (OR: 3.98, 95% CI: 2.52 – 6.29, p<0.0001) compared to those with normal lactate levels. Median ICU stay was 9.0 days (95% CI: 7.3–10.7) for the severely elevated lactate group, compared to 12.0 days for both the normal and elevated lactate groups. Multivariate logistic regression identified lactate level (OR=1.865, p=0.043) and APACHE-II score (OR=1.089, p=0.001) as independent predictors of mortality. Conclusion: Hyperlactatemia is predictor of disease severity and linked with higher odds of in-hospital mortality in comparison to normal lactate levels.